Unlocking the Power of the Franchising Format: Choosing the Right Franchisor - Ang, Rodolfo P (Archīum Ateneo, 2020)
Drawing from almost 30 years of experience, Sir Rudy Ang shares what the first steps of getting into the franchising business are. Speaker: Mr. Ang is currently the Dean of the Ateneo Graduate School of Business, has over thirty years of experience in the academe as an educator and leader, and has business interests in quick-service restaurant franchises and small scale commercial real estate development. He was the Dean of the John Gokongwei School of Management at the Ateneo de Manila University from 2003 to 2014. He is also a past President of the Alumni Association of Xavier School, and past Chairman of the Jollibee Franchisees Association. He completed his undergraduate studies at the Ateneo de Manila University, earning a double degree, AB Communications and BS Management (Honors program), Magna Cum Laude, in 1983. He earned his MBA at Boston College in 1988, graduating number one in his class. The Magisterial Lecture series is a collection of selected talks from Ateneo classes, delivered by some of the University’s most respected faculty members. They are produced and shared for the benefit of learners everywhere. Magisterial Lectures will be available on Areté’s YouTube channel for free. Magisterial Lectures is an Areté Production done in partnership with The Department of Communication, Loyola Schools and the Eugenio Lopez Jr. Center for Multimedia Communication.